Pharmacological blockade of adenosine A(2A) receptors diminishes scarring - Perez-Aso, Miguel (Federation of American Societies for Experimental Biology, 2012)
Adenosine A2A receptor (A(2A)R) stimulation promotes wound healing and is required for the development of fibrosis in murine models of scleroderma and cirrhosis. Nonetheless, the role of A(2A)R in the formation of scars following skin trauma has not been explored. Here, we examined the effect of pharmacological blockade of A(2A)R, with the selective adenosine A(2A)R-antagonist ZM241385 (2.5 mg/ml), in a murine model of scarring that mimics human scarring. We found that application of the selective adenosine A(2A)R antagonist ZM241385 decreased scar size and enhanced the tensile strength of the scar. Within the scar itself, collagen alignment and composition (marked reduction in collagen 3), but not periostin, biglycan, or fibronectin accumulation, was improved by application of ZM241385. Moreover, A(2A)R blockade reduced the number of myofibroblasts and angiogenesis but not macrophage infiltration in the scar. Taken together, our work strongly suggests that pharmacological A(2A)R blockade can be used to diminish scarring while improving the collagen composition and tensile strength of the healed wound.—Perez-Aso, M., Chiriboga, L., Cronstein, B. N. Pharmacological blockade of adenosine A(2A) receptors diminishes scarring.